Upaya Meningkatan Hasil Belajar Bahasa Inggris Siswa dalam Membaca Text Descriptive melalui Model Pembelajaran Role Playing di Kelas X IPS 2 SMA Negeri 1 Candung - Umniati Umniati (Journal on Education, 2022)
This study aims to find out and obtain information about How Efforts to Improve Students' English Learning Outcomes in Reading Descriptive Text Through Role Playing Learning Model in Class X IPS2 SMA Negeri 1 Candung. This type of research is classroom action research. The research subjects were students of class X IPS2 SMA Negeri 1 Candung with a total of 18 students. The time of this research is the odd semester of the 2021/2022 academic year which starts in September. This research procedure consists of two cycles with four stages of research, namely planning, implementing actions, observing and reflecting. Data collection techniques in this study were field notes, student worksheets, written tests, and documents. The collected data were analyzed using the percentage formula. The results of the study can be concluded that the learning process using the Role Playing Learning Model can improve students' English learning outcomes. Improved student learning outcomes can be seen from the pre-cycle, cycle I and cycle II